Off-tumor IDO1 target engagements determine the cancer-immune set point and predict the immunotherapeutic efficacy - Lulu Zhang; Yihai Cao; Lin Xie; Ming-Rong Zhang; Kuan Hu; Yanhong Duo; Takashi Shimokawa; Katsushi Kumata; Yiding Zhang; Cuiping Jiang; Nobuki Nengaki; Hidekatsu Wakizaka (Journal for ImmunoTherapy of Cancer)
Background Indoleamine-2,3-dioxygenase 1 (IDO1) has been intensively pursued as a therapeutic target to reverse the immunosuppressive cancer-immune milieu and promote tumor elimination. However, recent failures of phase III clinical trials with IDO1 inhibitors involved in cancer immunotherapies highlight the urgent need to develop appropriate methods for tracking IDO1 when the cancer-immune milieu is therapeutically modified.Methods We utilized a small-molecule radiotracer, 11C-l-1MTrp, to quantitatively and longitudinally visualize whole-body IDO1 dynamics. Specifically, we first assessed 11C-l-1MTrp in mice-bearing contralateral human tumors with distinct IDO1 expression patterns. Then, we applied 11C-l-1MTrp to longitudinally monitor whole-body IDO1 variations in immunocompetent melanoma-bearing mice treated with 1-methyl-l-tryptophan plus either chemotherapeutic drugs or antibodies targeting programmedcell death 1 and cytotoxic T-lymphocyte-associated protein 4.Results 11C-l-1MTrp positron emission tomography (PET) imaging accurately delineated IDO1 expression in xenograft mouse models. Moreover, we were able to visualize dynamic IDO1 regulation in the mesenteric lymph nodes (MLNs), an off-tumor IDO1 target, where the percentage uptake of 11C-l-1MTrp accurately annotated the therapeutic efficacy of multiple combination immunotherapies in preclinical models. Remarkably, 11C-l-1MTrp signal intensity in the MLNs was inversely related to the specific growth rates of treated tumors, suggesting that IDO1 expression in the MLNs can serve as a new biomarker of the cancer-immune set point.Conclusions PET imaging of IDO1 with 11C-l-1MTrp is a robust method to assess the therapeutic efficacy of multiple combinatorial immunotherapies, improving our understanding of the merit and challenges of IDO1 regimens. Further validation of this animal data in humans is ongoing. We envision that our results will provide a potential precision medicine paradigm for noninvasive visualizing each patient’s individual response in combinatorial cancer immunotherapy, and tailoring optimal personalized combination strategies.